Memory impairment in children with temporal lobe epilepsy: a review - Guimarães,Catarina A. (2006)
INTRODUCTION: The authors present a review article on memory aspects of temporal lobe epilepsy in childhood. METHODS: We performed a search in the literature. RESULTS: Temporal lobe epilepsy (TLE) in childhood present with great clinical, electroencephalographic and etiological diversity. The neuropsychological features in children with TLE are not well-defined yet. The relationship between the lateralization of the lesion and performance on memory tests is not established. CONCLUSION: The studies performed in children with TLE show controversy data. This finding may be due to the etiological, clinical and electroencephalographic diversity seen in such group of children. Besides, most studies use different assessments. Therefore, it is clear that more studies are necessary to elucidate which neuropsychological deficits occur in children with TLE.